Le rôle de l'État quant aux grandes orientations en matière énergétique - Garant, Patrice (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The State, whether at the federal or provincial levels, is deeply involved in the determination of the orientation of energy policy. It assumes a major role as « planner », « regulator », « producer » and « distributor ». One has first to take into account the constitutional context, that is the division of powers outlined in our Constitutional Acts of 1867 and 1982. There is now a complex balance of power which, although it appears to satisfy all parties, require considerable dialogue to work out. This is called at home and in other federal countries « cooperative federalism », with some federal para-mountcy nevertheless.